2011
DOI: 10.1590/s0103-50532011000800012
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and availability of copper, iron, manganese and zinc in the archaeological black earth profile from the Amazon region

Abstract: Os solos de terra preta arqueológica são ricos em matéria orgânica, contêm fragmentos cerâmicos e artefatos líticos e apresentam nutrientes em concentrações mais elevadas do que outros tipos de solos. Com o intuito de contribuir com informações sobre concentrações de micronutrientes disponíveis em solos de terra preta, foram avaliadas através de extrações químicas sequenciais, a distribuição e disponibilidade de Cu, Fe, Mn e Zn em um perfil de terra preta arqueológica no município de Juruti, estado do Pará. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…Total Mn was also twice as high in the hillfort compared to the unfertilized control and all fertilized treatments, which may be due to the deposition of biomass ashes, which can contain approximately from 1 to 3% of Mn (Brais et al, 2015; Kofman, 2016; Zając et al, 2018). Other authors have reported Mn accumulation because of the deposition of animal excrements and organic waste (e.g., Wilson et al, 2008; Mescouto et al, 2011; Vassilev et al, 2013). Among all elements identified in this study, the total content of Mn was most significantly positively correlated with total P ( r = 0.86, p < .001).…”
Section: Discussionmentioning
confidence: 95%
“…Total Mn was also twice as high in the hillfort compared to the unfertilized control and all fertilized treatments, which may be due to the deposition of biomass ashes, which can contain approximately from 1 to 3% of Mn (Brais et al, 2015; Kofman, 2016; Zając et al, 2018). Other authors have reported Mn accumulation because of the deposition of animal excrements and organic waste (e.g., Wilson et al, 2008; Mescouto et al, 2011; Vassilev et al, 2013). Among all elements identified in this study, the total content of Mn was most significantly positively correlated with total P ( r = 0.86, p < .001).…”
Section: Discussionmentioning
confidence: 95%
“…P persistence in tropical soils is associated to its high specific adsorption capacity onto iron (Fe) and aluminum (Al) oxides (Schaefer et al, 2004;Costa et al, 2017). Concentrations of Ca, Mg, Mn, Zn, and Cu in ADEs are also significantly higher in ADEs than in other Amazonian soils (Mescouto et al, 2011;Glaser and Birk, 2012;Schmidt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nadaska et al [9] studied environmental aspects of manganese using consecutive extraction and believed that this method gave accurate information about origin, occurrence way, bioavailability, potential mobility, and metals transfer in natural environments. Mescouto et al [10] showed that the highest concentration of iron and manganese is associated with residual fraction. Also, this study showed that, in fractions related to iron-manganese oxides, iron and manganese availability was in the range of 1265.139 to 1818.12 mg/kg and 48.51 to 83.0 mg/kg, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Mn in the form of organic matter bonded form increased by addition of compost from 0 to 15, 30, and 60 ton/ha at first and second years by 4.7, 23.76, 44.17, and 61.65, 67.26, and 73.54 percent (Figure 2). Mescouto et al [10] studied the distribution and availability of nutrients like Cu, Fe, Mn, and Zn according to Tessier consecutive extraction method and found that highest concentrations of nutrients are associated with residual fraction. Zheljazkov and Warman [31] studied the fractionation of Cu, Mn, and Zn in soils after application of two compost types, one resulting from municipal solid waste for sugar beet and basil and the…”
mentioning
confidence: 99%